An implication of e-commerce in textile and clothing industries: a relational Online Analytical Processing (OLAP) approach. (21st March 2008) - Lau, T.W.; Hui, C.L.; Ng, S.F.; Moon, K.L.; , G. Taylor
The current usage of electronic commerce in the Hong Kong textile and clothing industries is mainly at e mail communication according to the survey of the e commerce adoption in the local industries conducted in June 2001. It is a question of how to move the current position of e-commerce adoption towards the full electronic business integration in these industries. Achieving an integrated e-commerce system in the industries could be accomplished by adopting a state of-art information technology. However, it is too costly and lack of knowledge of such technology for widespread adoption by these industries. This study proposes a cost-effective method for providing an integrated solution of e-commerce in the industries, especially for small-and-medium sized enterprises. Based on the proposed method, a pilot system is developed for evaluation and the performance of the pilot system is accepted by the field practitioners. The outcomes of this study are worthwhile for the small- and medium-sized enterprises as it proposes a means to achieve an integrated e-commerce environment in the textile and clothing industries.